Dampak Gamifikasi Blooket terhadap Motivasi dan Pembelajaran Ekonomi - Erlin Zahroh Nuryani; Mohamad Arief Rafsanjani (Pusat Riset dan Inovasi Nasional, 2025)
Student motivation is an important factor that influences student engagement and academic achievement. Although many studies have examined learning motivation in classroom settings with non-interactive presentation media, limited research has explored how gamification affects motivation and learning outcomes in economics education. This study investigates the impact of using Blooket—a game-based learning platform—on students’ motivation and academic performance in economics classes during the 2024/2025 academic year. The study aims to: (i) evaluate the impact of Blooket on students’ learning motivation, (ii) assess the impact of Blooket on students’ learning outcomes. Data were collected through questionnaires and tests involving 40 high school students divided into experimental and control groups. The findings revealed that students taught using Blooket demonstrated significantly higher motivation and better learning outcomes compared to those taught using traditional methods. This study highlights the impact of the gamification medium 'Blooket' in fostering a more engaging and motivating learning environment, offering practical insights for educators seeking to enhance student participation and performance through digital tools.